Patterns of spatial variability for demersal fish communities on the shelf of the northwestern Bering Sea - Pavel Yu. Andronov; Andrey V. Datsky (Известия ТИНРО)
Six communities of demersal fishes and cyclostomes are identified on the shelf of the northwestern Bering Sea and their structure is described on the data of complex bottom trawl surveys conducted in 2004 and 2005. The communities include 110 species of fish and cyclostomes belonged to 27 families, mainly Cottidae, Pleuronectidae, Stichaeidae, Agonidae, Liparidae, Hemitripteridae, and Zoarcidae. Wide-boreal, arctic-boreal and high-boreal species of the eulittoral, mezobenthal and sublittoral complexes prevail, the most abundant ones walleye pollock, pacific sleeper shark, pacific cod, yellow irish lord, great sculpin, pacific herring, saffron cod, bering flounder, nothern rock sole, alaska plaice, butterfly sculpin, armorhead sculpin, and warty sculpin. The communities arrange in conformity with basic principles of bathymetric and latitudinal zonality, as is shown by multidimensional scaling clusterization. The spatial variability of ichthyocenes correlates stronger with depth - three communities are defined by bathymetry: sublittoral, elittoral, and upper-bathyal ones, and each of them can be divided into two communities of lower hierarchical level according to zoogeographical heterogeneity of the northwestern Bering Sea: one in the Anadyr Bay and other in the rest of the shelf. This arrangement did not change between 2004 and 2005.